2007
DOI: 10.1038/sj.emboj.7601626
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 and the Notch3-upregulated RNA-binding protein HuD regulate Ikaros alternative splicing

Abstract: Constitutive activation of the transmembrane receptor, Notch3, and loss of function of the hematopoietic transcription repressor, Ikaros (IK), play direct roles in T‐cell differentiation and leukemogenesis that are dependent on pre‐T‐cell receptor (pre‐TCR) signaling. We demonstrate the occurrence of crosstalk between Notch3 and IK that results in transcriptional regulation of the gene encoding the pTα chain of the pre‐TCR. We also show that, in the presence of the pre‐TCR, constitutive activation of Notch3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 40 publications
6
88
0
Order By: Relevance
“…In agreement with our present observations and with previous data demonstrating that Notch signaling activation in pre-T cells or in bone marrow results in the accumulation of CD4 þ CD8 þ DP cells in spleen and lymph nodes (Pear et al, 1996;Beverly et al, 2005;Bellavia et al, 2007), this feature being a characteristic of T-cell leukemia, we observed a decreased Notch3 protein expression specifically in splenic CD4 þ CD8 þ DP cells of TSA-treated mice. Therefore, it may be speculated that, by impairing N3 IC signaling, HDACi block the expansion or migration of CD4 þ CD8 þ cells, possibly representing the precursors of leukemic cells, in peripheral lymphoid organs and in circulating blood.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our present observations and with previous data demonstrating that Notch signaling activation in pre-T cells or in bone marrow results in the accumulation of CD4 þ CD8 þ DP cells in spleen and lymph nodes (Pear et al, 1996;Beverly et al, 2005;Bellavia et al, 2007), this feature being a characteristic of T-cell leukemia, we observed a decreased Notch3 protein expression specifically in splenic CD4 þ CD8 þ DP cells of TSA-treated mice. Therefore, it may be speculated that, by impairing N3 IC signaling, HDACi block the expansion or migration of CD4 þ CD8 þ cells, possibly representing the precursors of leukemic cells, in peripheral lymphoid organs and in circulating blood.…”
Section: Discussionsupporting
confidence: 93%
“…TSA-induced downregulation of Notch3 prevents T-ALL development and progression in N3 IC tg mice The role of Notch3 acetylation in enhancing protein degradation would be consistent with the subsequent suppression of Notch3-dependent transcriptional activity and activation of a number of proliferative or oncogenic pathways (Talora et al, 2003(Talora et al, , 2006Vacca et al, 2006;Bellavia et al, 2007). Overall, these findings suggest that this acetylation mechanism might be exploited for controlling Notch3-dependent leukemia.…”
Section: Notch3 Acetylation Impairs T-cell Proliferationmentioning
confidence: 55%
See 2 more Smart Citations
“…c-Cbl activity in Notch3-dependent leukemia S Checquolo et al Notch3 and pTa association was also detected in 2017 pre-T-cell line (Spolski et al, 1988) that express high level of both Notch3 and pTa (Bellavia et al, 2007) (Figure 4e, right panel). Altogether these observations suggest that the interaction of Notch3 and pTa proteins is possible at the cell surface of thymocytes, where the lipid rafts represent the molecular platform in which TCR or pre-TCR components cluster to trigger intracellular signaling.…”
Section: Introductionmentioning
confidence: 77%